The high burden of erectile dysfunction among men living with HIV in northern Tanzania: a call for evidence-based interventions - Mbwambo, Orgeness J.; Lyatuu, Moses; Ngocho, Geofrey; Abdallah, Khadija; Godfrey, Patricia; Ngowi, Bartholomeo N.; Mremi, Alex; Malindisa, Evangelista; Amour, Maryam; Ngocho, James; Balandya, Emmanuel; Kwesigabo, Gideon; et al. (Frontiers in Urology, 2023)
Background The extent of the burden of erectile dysfunction and its associated factors remains unclear. The aim of this study was to investigate the factors associated with ED and its prevalence among MLHIV in northern Tanzania. Methods A hospital-based, multi-center, cross-sectional study was conducted on MLHIV aged 18 years and above in northern Tanzania. Outcome The risk factors for ED and the prevalence of such risk factors among MLHIV was assessed and evaluated through a multivariate logistic regression analysis adjusted for depression symptoms using the Patient Health Questionnaire-9 (PHQ9) scale; anxiety disorders using the Generalized Anxiety Disorder Assessment (GAD-7); ART adherence; viral load; initial regimen date; ART regimen; and sexual risk behaviors. Results Data for 366 participants with a median age of 50 years (IQR 38–57 years) were available for analysis. Approximately three in four (74.6%) MLHIV had ED (of any severity), whereas 37.7% had mild ED. The majority (96.5%) of the participants had low testosterone, two in three (66.7%) had depressive symptoms, and close to half of the participants (48.4%) had anxiety. Age, lack of engagement in vigorous physical activity, depression, and self-reported good adherence to antiretroviral therapy (ART) were associated with ED in a multivariate logistic regression analysis (p=0.004, p =0.006, p=0.07, p=0.006, and p=0.004, respectively). Conclusion There is a high prevalence of ED among MLHIV in northern Tanzania. Erectile dysfunction should be regarded as one of the comorbidities associated with HIV and should be routinely screened for among MLHIV in CTC clinics.